Russian cuisine in exile - Vaĭlʹ, Petr, 1949-2009; Geni, Alexander (Academic Studies Press, 2018)
Russian Cuisine in Exile brings the essays of Pyotr Vail and Alexander Genis, originally written in the mid-1980s, to an English-speaking audience. A must-read for scholars, students and general readers interested in Russian studies, but also for specialists in émigré literature, mobility studies, popular culture, and food studies. These essays--beloved by Russians in the U.S., the Russian diaspora across the world, and in post-Soviet Russia--narrate everyday experiences and re-imagine the identities of immigrants through their engagement with Russian cuisine. Richly illustrated and beautifully produced, the book has been translated "not word for word, but smile for smile," to use the phrase of Vail and Genis's fellow émigré writer Sergei Dovlatov. Translators Angela Brintlinger and Thomas Feerick have supplied copious authoritative and occasionally amusing commentaries